Eksistensi Kursus Musik Terhadap Kualitas dan Kuantitas Siswa - Ananda, Fazrin Sheila; Kurnia, Sri Ayu; Rusmana, Nandang; Hyangsewu, Pandu (Mahesa Research Center, 2024)
This research examines the development of music course institutions in Indonesia in the last decade, focusing on their management and strategies to maintain their sustainability and existence. Music course institutes that offer a range of skills, such as vocal, piano, guitar and violin, are now growing, adopting national and international curricula. This research highlights the importance of quality management in ensuring the sustainability of music course institutions, including aspects of legality, competent organizational structure, and adequate capital base. Through literature study, observation, and interviews with owners and managers of music courses in Bandung and Cimahi, it was found that factors such as sustainability of the organization, effective learning process, innovation in teaching methods, as well as improving the quality of human resources and facilities play an important role in maintaining the existence of the institution. The results provide insights into the importance of balancing quantity and quality in the management of music course institutions, and offer effective strategies for other music course managers to attract the public and maintain the sustainability of their businesses. The study also identifies areas for further research and acknowledges the limitations that exist within the scope of this study.